Depressive disorder among the end-stage renal disease patients undergoing maintenance hemodialysis at Chitwan medical college - Dahal, Sabina; Sedhai, C.P. (Journal of Psychiatrists' Association of Nepal, 2023)
Background: Patients with End stage renal disease (ESRD) suffer from a variety of losses, including renal function, family role, work role, sexual function, as well as time and mobility, all of which have a substantial influence on their lives. Physical manifestation of the End-Stage Renal Disease patients receiving dialysis treatment may be obvious but studies have found that they are also at increased risk of clinical and subclinical Depressive Disorder for a variety of reasons; which might be overlooked in our routine clinical assessment. Depressive Disorder has been associated with impaired recovery and increased mortality in many diseases including End-Stage Renal Disease patients. Objectives: To assess the magnitude of depressive disorder among the patients undergoing hemodialysis of duration >3 months at Chitwan Medical College Teaching Hospital (CMCTH) and to determine the association between explanatory variables with depressive disorder. Methods: Patients undergoing maintenance hemodialysis at CMCTH after meeting inclusion criteria were enrolled by consecutive sampling technique. Diagnoses were assessed on the basis of the ICD-10 Classification of Mental and Behavioral Disorders- Diagnostic Criteria for Research (ICD-10 DCR). To stratify the severity of the Depression into mild, moderate and severe categories, we used Hamilton Depressive Disorder rating scale. Seventy-four (74) patients undergoing maintenance hemodialysis were assessed. Interviews with patients and informants were taken and filled in a self-designed demographic datasheet. Obtained data were analyzed by using descriptive and inferential statistics. Results: The prevalence of the depressive disorder among patients undergoing maintenance hemodialysis was 75.70%. Positive correlations were found between depressive disorder and gender, age group and occupation(p<0.05). Conclusion: The present study showed that the prevalence of depressive disorder was higher in ESRD patients compared to study done in Nepal where prevalence of depressive disorder in ESRD patients was 51.8%.